Pembuatan Prototype Main L.O System Pada Sump Tank Di Mesin Induk 2 Tak - Bagas Dwi Andika; Amad Narto; Febria Sujarman (Sekolah Tinggi Maritim Yogyakarta, 2021)
In this modern era in the maritime world, the learning process related to ship engineering is very necessary and very important for students to master. So, many effective learning methods are used, one of which is the learning method using props on board. Therefore, this study aims to find out how to make props and to find out the working principles of teaching aids and to find out the benefits obtained from teaching aids. The type of props made by the author is the Main L.O System props on the Sump Tank on the 2-Stroke Main Machine. The method used is Research and Development, which is a process or steps to develop a new product or improve an existing product, be it hardware or software. The model in this development research is a procedural model, which outlines the steps of making that are exposed sequentially and gradually from the beginning to the end. This trainer uses a material made of clear resin which is shaped to resemble the working steps of a 2 stroke main engine which also features its lubrication system. The working system of this trainer is a lubrication system from the sump to the sump that uses a water pump to circulate the flow.